Mafia and Union. Once Upon a Time, America (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
The essay historically examines the relationship between the Mafia and labor unions in the United States, focusing on those personalities who contributed most, in the history of America in the 20th century, to countering the growing infiltration of organized crime into the union world. The analysis focuses on the contribution provided, between the 1930s and the 1960s, by Thomas Dewey, District Attorney in New York since 1935, and Bobby Kennedy, first as legal adviser for the first Senatorial Commission of Inquiry into organized crime and corruption in labor unions and later as head of the Justice Department in his brother John Fitzgerald Kennedy’s administration
Keywords: mafia; union; United States; Thomas Dewey; Bobby Kennedy